Tickling APCsThe p84/p110 complex of PI3K regulates NOX2 assembly and cross-presentation of immune complexes. (October 2022) - Adiko, Aimé Cézaire; Bens, Marcelle; Tandon, Naman; Benadda, Samira; Boedec, Erwan; Pellé, Olivier; El-Benna, Jamel; Monteiro, Renato; Laffargue, Muriel; Stephens, Len; Guermonprez, Pierre; Saveanu, Loredana
Abstract : Antibody-mediated cross-presentation is known to elicit strong CD8 + T cell responses, particularly relevant in cancer therapy. Anti-tumor antibodies are known to rapidly kill cancer cells by antibody-dependent cellular cytotoxicity (ADCC), but the long-term immune control of tumors is based on induction of CD8 + T cell response, which relays on anti-tumor antibody-mediated cross-presentation. The molecular mechanisms by which this pathway of cross-presentation allows to poor cross-presenting cells, such as type 2 dendritic cells (DCs) and monocyte-derived DCs (moDCs), to efficiently cross present are not well understood. We demonstrated that enzymatic activity of p84/p110g complex of PI3Kg regulates the assembly of NADPH oxidase NOX2 and ROS production in type 2 DCs from mouse spleen and murine bone marrow derived DCs, enhancing thus the cross-presentation of immune complexes by these cells. Our results suggest that the association between anti-tumor monoclonal antibodies and PI3Kg inhibitors might block the antibody-mediated cross-presentation of tumor antigens and should be avoided in clinical therapy of cancers.